A novel approach of synthesizing nano Y2O3 powders for the fabrication of submicron IR transparent ceramics. Issue 12 (15th June 2021) - Kumar, R. Senthil; Priyanka, K.H. Sai; Khanra, A.K.; Johnson, R.
Abstract: A facile methodology of synthesizing highly reactive, round-edged, Sulfur–free nano Y2 O3 powders to fabricate submicron IR transparent yttria ceramics having a unique combination of superior optical and mechanical properties are reported for the first time. Dispersion of yttrium hydroxide into aqueous sol and addition of seed particles produced near-spherical yttria powders having non – aggregated particles with narrow size distribution. The powder exhibited excellent sinterability reaching near-theoretical density at temperatures around 1400 °C in air. Effective inter-particle coordination and traces of Al additives assisted achieving superior densification. Sintered specimens showed average grain sizes closer to 700 nm. Post-sinter hot isostatic pressing eliminated the residual porosity from the sintered samples leading to exhibit IR transmissions up to 84% in the 2.0–9.0 μm regions, equivalent to single crystal Y2 O3 . Achieving densification through solid-state sintering and retaining the sintered grain sizes in the submicron regions significantly enhanced the mechanical properties. Sintered and HIPed Y2 O3 specimens were further characterized for their thermal properties at temperature regions between ambient to 950 °C.